The adventure zone. [5], The eleventh hour - McElroy, Clint, 1955-; Pietsch, Carey; McElroy, Griffin (First Second, 2023)
"The Bureau of Balance has located yet another Grand Relic, and this time it's...time? A small mining town called Refuge has been locked away behind an arcane bubble, and somewhere inside it the Temporal Chalice is causing unknown mayhem. Taako, Magnus, and Merle are launched into their investigation, but they've barely had a chance to get their feet under them before the situation literally falls apart. When the town clocktower strikes noon, Refuge and its citizens are destroyed in a sudden chaos of flame and ruin, and our heroes' relic hunting--along with their lives--comes to an abrupt end. But woah, what's this? It's 11AM, they're alive again, and Refuge definitely hasn't just been exploded? Looks like a classic time loop, friends. This town is trapped in its final hour, and so are the three of them. And in order to escape, they'll not only have to solve the mystery of what happened to the Chalice, they'll also also have to resist what it offers: the chance to rewrite the worst days of their own pasts."--Provided by publisher